The metastasis-associated protein S100A4 exists in several charged variants suggesting the presence of posttranslational modifications - Flatmark Kjersti; Haugen Mads H; Mikalsen Svein-Ole; Malandsmo Gunhild M (BMC Cancer, 2008)
Abstract Background S100A4 is a metastasis-associated protein which has been linked to multiple cellular events, and has been identified extracellularly, in the cytoplasm and in the nucleus of tumor cells; however, the biological implications of subcellular location are unknown. Associations between a variety of posttranslational protein modifications and altered biological functions of proteins are becoming increasingly evident. Identification and characterization of posttranslationally modified S100A4 variants could thus contribute to elucidating the mechanisms for the many cellular functions that have been reported for this protein, and might eventually lead to the identification of novel drugable targets. Methods S100A4 was immuoprecipitated from a panel of in vitro and in vivo sources using a monoclonal antibody and the samples were separated by 2D-PAGE. Gels were analyzed by western blot and silver staining, and subsequently, several of the observed spots were identified as S100A4 by the use of MALDI-TOF and MALDI-TOF/TOF. Results A characteristic pattern of spots was observed when S100A4 was separated by 2D-PAGE suggesting the presence of at least three charge variants. These charge variants were verified as S100A4 both by western immunoblotting and mass spectrometry, and almost identical patterns were observed in samples from different tissues and subcellular compartments. Interestingly, recombinant S100A4 displayed a similar pattern on 2D-PAGE, but with different quantitative distribution between the observed spots. Conclusion Endogenously expressed S100A4 were shown to exist in several charge variants, which indicates the presence of posttranslational modifications altering the net charge of the protein. The different variants were present in all subcellular compartments and tissues/cell lines examined, suggesting that the described charge variants is a universal phenomenon, and cannot explain the localization of S100A4 in different subcellular compartments. However, the identity of the specific posttranslational modification and its potential contribution to the many reported biological events induced by S100A4, are subject to further studies.